Eksplorasi Pengaruh Kesediaan Membayar Layanan Logistik Halal terhadap Perpanjangan Sertifikat Logistik Halal: UMKM Sektor Pertanian - Muhammad Dzulfaqori Jatnika; Listia Andani; Faqihuddin; Cici Aulia Permata Bunda (JURNAL AGROINDUSTRI HALAL, 2023)
The first period of halal certification obligations according to Undang-Undang Nomor 33 Tahun 2014 and its derivatives will end on October 17, 2024, including food and beverage products. Therefore, the halal certification process for products of micro, small, and medium enterprises needs to be carried out promptly. The aim of this research is to examine the factors influencing the willingness of agricultural commodity-based UMKM players to pay for halal logistics services. This study employs a quantitative approach with purposive sampling for data collection and SEM-PLS for data analysis. The research includes 350 respondents who are UMKM players based on agricultural commodities. The findings of this study reveal that, in addition to the variable knowledge on halal, other variables such as concern on halal, awareness on halal, perception of halal logistics, and service capability have a positive and significant influence on the willingness to use halal logistics services. Furthermore, the willingness to use halal logistics services can encourage halal logistics service providers to renew their halal logistics certificates. The research findings will be beneficial for policymakers and managers of halal logistics companies as it helps them understand the factors that drive the adoption of halal logistics services.